Environmental impacts of dairy farming in Lembang, West Java - Vries, Marion de; Wouters, A.P.; Vellinga, Theun V. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
The demand for milk and dairy products is growing in Indonesia. At the same time, Indonesia has committed itself to substantially reduce national greenhouse gas (GHG) emissions. Low- emission strategies are required to sustainably increase milk production of the Indonesian dairy sector. Objectives of this study were to estimate the current level of GHG emissions and land use of dairy farms in Lembang District, West Java, and evaluate the potential effects of feeding and manure management interventions on GHG emissions and land use. A life cycle assessment was used to estimate cradle-to-farm gate GHG emissions and land use of an average dairy farm in Lembang District, using data from a survey of 300 dairy farmers in Lembang in 2016. Total GHG emissions were 33 ton CO2e. per farm/year, and emission intensity was 1.9 kg CO2e per kg of fat and protein corrected milk (FPCM) and 8.8 kg CO2e per kg live weight. Total estimated land use was 2.1 ha per dairy farm, which was equal to 1.2 m2 per kg FPCM and 5.6 m2 per kg live weight. Hotspots of GHG emissions were rumen enteric fermentation (CH4), manure management (CH4 and N2O; especially discharged manure), and off-farm feed production (CH4, N2O and CO2; especially rice straw). Feeding and manure management interventions evaluated in a scenario analysis in this study changed total GHG emissions by -12 to +24%, and GHG emission intensity by -1 to -14%. Total land use changed by -6 to +22%, and land use intensity (i.e., land use per kg FPCM or life weight) by 0 to -11%. Largest reductions in GHG emission intensity were found in the scenarios with maize silage feeding, improved manure management, and an increased amount of roughage in the diet. We concluded that improvement of feeding and manure management can reduce GHG emissions and land use of dairy farms in Lembang District. As results were based on scenario analysis, the mitigation potential of interventions should be validated in practice.